INDONESIAN EFL LEARNERS’ LEARNING STYLE AND THEIR IMPACTS ON THEIR SELF-EFFICACY - Alfian, Heri; Muhammad Basri; Sultan (English Language, Linguistics, and Culture International Journal, 2023)
The objectives of the study were to find out (1) the kinds of learning style of Indonesian EFL learners, (2) the impacts of Indonesian EFL learners’ learning style towards their self-efficacy in terms of their stress, and (3) the impacts of Indonesian EFL learners’ learning style towards their self-efficacy in terms of their self-confidence. This study employed a case study design. The participants of this study consisted of 30 students of the second semester of English Department, Unismuh Makassar academic year 2016-2017. The data were obtained through questionnaire, observation, and interview. The data of questionnaire were analyzed, tabulated and dropped into percentage while the data of observation and interview were analyzed based on procedure of data analysis that consisted of the data collection, the data display, data condensation and conclusion: drawing/ verification. The results of the study indicated that among 30 participants, 10 students (33.33%) are visual, 8 students (26.66%) are auditory, 8 students (26.66%) are kinesthetic, 3 students (10%) are visual and kinesthetic, and 1 student (3.33%) is auditory and kinesthetic. Indonesian EFL learners’ learning style impacted their self-efficacy through information of self-skill as one of six factors influenced self-efficacy. In terms of stress and self-confidence learning style impacted Indonesian EFL learners’ self-efficacy through selection and motivation process, mastery experience, and dimension of strength as the features of self-efficacy. In addition, learners’ learning style could not match with every method used by the teacher/lecturer in the class. Also, stress is appeared when the method did not engage the needs of the learners’ learning style and learners show their self-confidence when the method used by the teacher/lecturer supports their learning style. Keywords: Learning style, self-efficacy, stressful, self-confidence